La netnographie d’une communauté en ligne en lutte contre la « censure » sur un forum français populaire - Olivier PERIA (Tic & Société)
Through a case study of a popular French forum, this article aims to understand how speech moderation is received, criticized and countered by the cybercommunity, in particular by its most visible and virulent factions, largely influenced by and linked to the "fachosphere". The aim is to contribute to a critical reflection on the means and techniques of discourse regulation on social networking platforms, as well as the circumvention strategies implemented by a diversity of actors seeking to subvert the public spaces of "open societies" from within. First, I emphasize the victim ideology developed on the forum. Then I discuss several efficient circumvention strategies implemented by the forum’s far-right sub-community to circumvent censorship and how this helps cultivate a collective identity and a sense of belonging to the group. Finally, I show that censorship may lead participants to 'migrate' to other, more fringe spaces promoting almost total freedom of speech.